2015
DOI: 10.1128/iai.00360-15
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of TP0126, Treponema pallidum Putative OmpW Homolog, Is Regulated by the Length of a Homopolymeric Guanosine Repeat

Abstract: An effective mechanism for introduction of phenotypic diversity within a bacterial population exploits changes in the length of repetitive DNA elements located within gene promoters. This phenomenon, known as phase variation, causes rapid activation or silencing of gene expression and fosters bacterial adaptation to new or changing environments. Phase variation often occurs in surface-exposed proteins, and in Treponema pallidum subsp. pallidum, the syphilis agent, it was reported to affect transcription of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 67 publications
1
60
0
Order By: Relevance
“…The picture emerging from our evolving concepts of the spirochete’s molecular architecture is multi-factorial and likely involves copious production of antibodies against subsurface lipoprotein ‘decoys’ 57,110 ; poor target availability owing to low copy numbers of outer membrane proteins and surface-exposed lipoproteins 67,77,82,84,93 ; in the case of bipartite outer membrane proteins, limited production of antibodies against surface-exposed epitopes along with skewed production of antibodies against periplasmic domain 84,93 ; organism-to-organism variation in the levels of expression of outer membrane proteins and outer surface lipoproteins through a variety of mechanisms, including phase variation 82,92,115,116 ; and, in the case of TprK, antigenic variation as a result of intra-genomic recombination 89,92,117 . Additionally, the ability of motile spirochetes to ‘outrun’ infiltrating phagocytes and reach sequestered locations, including the epidermis, could be an under-appreciated aspect of immune evasion 10,102 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…The picture emerging from our evolving concepts of the spirochete’s molecular architecture is multi-factorial and likely involves copious production of antibodies against subsurface lipoprotein ‘decoys’ 57,110 ; poor target availability owing to low copy numbers of outer membrane proteins and surface-exposed lipoproteins 67,77,82,84,93 ; in the case of bipartite outer membrane proteins, limited production of antibodies against surface-exposed epitopes along with skewed production of antibodies against periplasmic domain 84,93 ; organism-to-organism variation in the levels of expression of outer membrane proteins and outer surface lipoproteins through a variety of mechanisms, including phase variation 82,92,115,116 ; and, in the case of TprK, antigenic variation as a result of intra-genomic recombination 89,92,117 . Additionally, the ability of motile spirochetes to ‘outrun’ infiltrating phagocytes and reach sequestered locations, including the epidermis, could be an under-appreciated aspect of immune evasion 10,102 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…We showed that in the initial T. pallidum Nichols strain genome (24), the tp0126 open reading frame (ORF) was incorrectly annotated as a longer polypeptide and was therefore not predicted to have a cleavable signal sequence for sorting to the outer membrane (24). A cleavable signal peptide could, however, be easily predicted after we experimentally identified the gene transcriptional start site (TSS) and most likely start codon (24). Moreover, analysis of circular dichroism (CD) spectra produced by recombinant Tp0126 following protein refolding suggested that the percentages of ␤-barrel (43%), ␣-helix (30%), and random-coil (27%) components were compatible with a ␤-barrel OMP, further supporting the structural homology of Tp0126 to OmpW (24).…”
mentioning
confidence: 98%
“…However, OMP identification has been hindered by several limitations associated with working with T. pallidum in a laboratory setting, including the unusual fragility of the pathogen's OM and the inability to genetically manipulate this bacterium (1). Analysis of annotated proteomes of T. pallidum strains using bioinformatics tools has therefore been of pivotal importance to identify proteins bearing sequence/structural homology to known prokaryotic OMPs (22)(23)(24). Continued research efforts to deepen our knowledge on these proteins are, however, necessary, particularly because sufficient experimental data to label most of these in silico-identified proteins as bona fide OMPs are still lacking, and independent studies have sometimes led to discordant conclusions on the location and/or structure of some OMP candidates (25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of T. pallidum to evade the host immune response is attributed to the organism’s scarcity of surface-exposed outer membrane proteins (OMPs), very slow generation time (∼33h), and the ability to stochastically and rapidly switch on and off expression of genes encoding putative OMPs through phase variation [9]. Chief among the immune evasion strategies evolved by T. pallidum is its ability to generate diversity within the putative OMP TprK [1012].…”
Section: Introductionmentioning
confidence: 99%